2015
DOI: 10.1108/jsbed-08-2012-0099
|View full text |Cite
|
Sign up to set email alerts
|

Funding accessibility for minority entrepreneurs: an empirical analysis

Abstract: Purpose – The purpose of this paper is to examine what factors affect entrepreneurs with minority background to access public financial institutions’ funds in initiating and developing their new ventures. Following the signal theory, social capital theory and the liability of newness perspective, the effect of demographic characteristics of entrepreneurs were investigated and the differences between ethnic minority and non-minority entrepreneurs’ access to financial institutions’ funds were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 69 publications
(87 reference statements)
0
50
0
Order By: Relevance
“…Low educational level and lack of prior experience are among the factors that decrease their chances to obtain financial aid, especially from public financial institutions (Bewaji, Yang, & Han, 2015). Another factor is the lack of familiarity with the local business environment.…”
Section: Immigrant Entrepreneurial Issues and Obstaclesmentioning
confidence: 99%
“…Low educational level and lack of prior experience are among the factors that decrease their chances to obtain financial aid, especially from public financial institutions (Bewaji, Yang, & Han, 2015). Another factor is the lack of familiarity with the local business environment.…”
Section: Immigrant Entrepreneurial Issues and Obstaclesmentioning
confidence: 99%
“…They added that they preferred to keep a good bank record, which enabled them to get loans. Previous studies have also showed that accessing loans from banks or other financial institutions is often harder for minorities than non-minorities [98]. This can be due to banks' preference for long-term customers or loan applications with familiar references.…”
Section: Internal and Financial Resourcesmentioning
confidence: 99%
“…Accordingly, one of the main success factors of new venture development is access to capital [103,104]. Lack of financial capital is claimed to be a key barrier for immigrant entrepreneurs [98]. Financial capital can come in different forms such as savings, loans from banks and financial institutions and various funding sources [98].…”
Section: Undercapitalizationmentioning
confidence: 99%
See 2 more Smart Citations